Key role of reactive oxygen species-scavenging system in nitric oxide and hydrogen sulfide crosstalk-evoked thermotolerance in maize seedlings - Sun, Yu-Ying; Wang, Jia-Qi; Xiang, Ru-Hua; Li, Zhong-Guang (Frontiers in Plant Science, 2022)
Nitric oxide (NO) and hydrogen sulfide (H2S) are novel signaling molecules, which participate in plant growth, development, and response to stress. In this study root-irrigation with 0.15 mM sodium nitroprusside (SNP, NO donor) up-regulated gene expression of L-CYSTEINE DESULFHYDRASE1 (LCD1), activities of L-cysteine desulfhydrase (LCD) and D-cysteine desulfhydrase (DCD), as well as an endogenous H2S level, compared to control seedlings. The SNP-up-regulated effects were enhanced by 0.5 mM sodium hydrosulfide (NaHS, H2S donor), but weakened by NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) and H2S scavenger hypotaurine (HT) alone. NaHS had no significant effect on gene expression and activity of nitrate reductase (NR, a NO candidate producing enzyme). These data indicate that NO could trigger the LCD/H2S signaling pathway in maize seedlings. To further investigate the effect of NO and H2S crosstalk on thermotolerance in maize seedlings, thermotolerance parameters and reactive oxygen species (ROS)-scavenging system were estimated. The results show that SNP increased survival rate and tissue viability, decreased malondialdehyde (MDA) accumulation, and electrolyte leakage in maize seedlings under heat stress (HS), implying NO could improve thermotolerance in maize seedlings. The NO-improved thermotolerance was impaired by H2S inhibitor DL-propargylglycine (PAG) and scavenger HT alone. Similarly, SNP up-regulated the gene expression of DEHYDROASCORBATE REDUCTASE (DHAR) and GLUTATHIONE REDUCTASE1 (GR1); activities of ascorbate peroxidase, glutathione reductase, and catalase; as well as levels of ascorbic acid, glutathione, flavonoids, carotenoids, and total phenols. SNP also reduced hydrogen peroxide and superoxide radical accumulation in maize seedlings under HS compared to the control. The effects of SNP on ROS and their scavenger system were weakened by PAG and HT alone. These data hint that NO could evoke thermotolerance in maize seedlings by triggering the LCD/H2S signaling pathway, and the ROS-scavenging system played a key role in the NO and H2S crosstalk-evoked thermotolerance.